Emily Jeremiah. Nomadic Ethics in Contemporary Women’s Writing in German: Strange Subjects. Rochester, NY: Camden House, 2012. 232 pp. - Brooke D. Kreitinger (Studies in 20th & 21st Century Literature, 2015)
Review of Emily Jeremiah. Nomadic Ethics in Contemporary Women’s Writing in German: Strange Subjects. Rochester, NY: Camden House, 2012. 232 pp.
Keywords: German-language literature; feminist ethics; feminist aesthetics; epistemology; globalization; subjectivity; national identity; postmemory